Comparison of Different Phase-Shift Control Methods at Isolated Bidirectional DC-DC Converter - Ilker Kayaalp; Tugce Demirdelen; Tahsin Koroglu; M. Ugras Cuma; K. Cagatay Bayindir; Mehmet Tumay (International Journal of Applied Methods in Electronics and Computers, 2016)
In this study, the operation, design and comparison of single, extended and dual phase shift control methods on bidirectional DC-DC converters are discussed. The major components (DC link capacitors and inductors) are derived for different phase shifting methods in order to obtain maximum efficiency. Triggering signals, voltages and current waveforms are compared for buck-boost conditions through PSCAD simulation results on the single-phase full-bridge converter topology with isolation transformer.